Natural reduction of graphene oxide to graphene using kaffir lime leaves extract - Chan, Bun Hoo (2014)
Since the reduction of graphene from graphene oxide was early investigate for successful in chemical reduction method using hydrazine and dextran, thermal reduction and also using vitamin C. In this proposal, natural reduction of graphene from graphene oxide is presented by natural reduction for performing higher reduction rate. Graphene oxide was prepared using the method form a part of Hummers Method. Graphite will oxidize to graphene oxide and synthesis to graphene oxide. Then graphene oxide will be reduce for using natural reduction by using kaffir lime leaves extract. Optimization of the reductant concentration and minimum reduction time to produce highest reduction rate was done in this research by the parameter of retention time and kaffir lime leaves extract concentration. The electrochemical properties and the functionalized carbon nanosheets analysis of graphene are examined by the Scanning Electron Microscopy (SEM).